Do Multifinance Institutions Matter for Poverty Reduction? Evidence from Indonesia - Laksmi , Ni Kadek; Soseco, Thomas (Department of Development Economics, Universitas Sriwijaya, 2024)
Microfinance Institutions (MFIs) can help reduce poverty by offering small loans to people who cannot get bank loans due to lack of collateral. However, in Indonesia, access to microfinance institutions is unequally distributed, as shown by the establishment of MFIs in Indonesia, which covers only 22 out of 34 provinces. This condition limits their impact on poverty reduction. This study examines how access to MFIs and the loans they provide affect poverty rates in Indonesia, using cross-sectional data from 22 provinces between 2016 and 2022. The results show that access to MFIs and the loans they provide do not significantly reduce poverty. This is due to poor infrastructure, low-quality MFI services, and insufficient loan amounts. The study also found that education lowers poverty, unemployment increases it, and agriculture helps reduce it. To improve poverty reduction, the government should improve infrastructure and extend MFI coverage to more provinces. Additionally, MFIs should increase their loan amounts to make a bigger impact.